Characterization of human stem cell-derived hepatic stellate cells and liver sinusoidal endothelial cells during extended in vitro culture - Wilhelmsen, Ingrid; Amirola Martinez, Mikel; Stokowiec, Justyna; Wang, Chencheng; Aizenshtadt, Aleksandra; Krauss, Stefan (Frontiers in Bioengineering and Biotechnology, 2023)
Background: There is a significant need for predictive and stable in vitro human liver representations for disease modeling and drug testing. Hepatic stellate cells (HSCs) and liver sinusoidal endothelial cells (LSECs) are important non-parenchymal cell components of the liver and are hence of relevance in a variety of disease models, including hepatic fibrosis. Pluripotent stem cell- (PSC-) derived HSCs (scHSCs) and LSECs (scLSECs) offer an attractive alternative to primary human material; yet, the suitability of scHSCs and scLSECs for extended in vitro modeling has not been characterized. Methods: In this study, we describe the phenotypic and functional development of scHSCs and scLSECs during 14 days of 2D in vitro culture. Cell-specific phenotypes were evaluated by cell morphology, immunofluorescence, and gene- and protein expression. Functionality was assessed in scHSCs by their capacity for intracellular storage of vitamin A and response to pro-fibrotic stimuli induced by TGF-β. scLSECs were evaluated by nitric oxide- and factor VIII secretion as well as endocytic uptake of bioparticles and acetylated low-density lipoprotein. Notch pathway inhibition and co-culturing scHSCs and scLSECs were separately tested as options for enhancing long-term stability and maturation of the cells. Results and Conclusion: Both scHSCs and scLSECs exhibited a post-differentiation cell type-specific phenotype and functionality but deteriorated during extended culture with PSC line-dependent variability. Therefore, the choice of PSC line and experimental timeframe is crucial when designing in vitro platforms involving scHSCs and scLSECs. Notch inhibition modestly improved long-term monoculture in a cell line-dependent manner, while co-culturing scHSCs and scLSECs provides a strategy to enhance phenotypic and functional stability.